Heavy Metals Characterization of Sludge from a Philippine Recycling Paper Mill - Lorraine A. Carrillo; Susan M. Gallardo (Department of Chemical Engineering, Universitas Gadjah Mada, 2004)
Wastewater treatment sludge, which is the largest volume residual waste stream generated by the pulp and paper industry, is generally disposed of in a dedicated landfill. Composting the sludge is an alternative method proposed by the Asian Regional Research Program on Environmental Technology-De La Salle University (ARRPET-DLSU) Minor Issue Group. The Philippine Department of Agriculture's (DA) standards for an organic fertilizer's maximum allowable content of heavy metals provided the legislative regulation for the conversion of sludge to compost. The research was designed to characterize the sludge samples from TIPCO, a Philippine paper-recycling mill, and establish whether the sludge contained the heavy metals cadmium, chromium, lead, mercury, nickel, and zinc using atomic absorption spectrophotometer (MS). Sampling was done for four weeks during newsprint and white paper production. Three discharge terminals were established as sampling points. The samples showed that the metal content of the sludge vary from point to point and was highest throughout the manufacture of white paper. Chromium, mercury, and nickel, however, were nondetectable in all the samples, while cadmium was detectable only in very few samples. Lead and zinc were present at all three points and were highest at the de inking sludge. Comparing the results with Part 503 of the United States EPA and the DA's guidelines for organic fertilizers yield significantly lower parameter values. Composting the sludge was, therefore, found to be a feasible option for recycling paper-mill sludge since the metal content were very low compared to local and international standards.